The relationship between practice environment, job satisfaction and intention to leave in critical care nurses - Alenazy, Faisal S.; Dettrick, Zoe; Keogh, Samantha (Nursing in critical care, 2023)
Background Recent studies in the Kingdom of Saudi Arabia (KSA) have shown that the increasing nursing turnover in the health care industry has become a great source of concern. The overdependence on the supply of expatriate nurses (74%) and coronavirus disease 2019 (COVID‐19) travel restrictions have exacerbated this staffing issue. Aims To examine the relationship between perception of nursing practice environment (NPE), job satisfaction and intention to leave (ITL) among critical care nurses working in the state of Ha'il in KSA. Design Cross‐sectional correlational (observational) design. Methods Data were collected via electronic online survey distributed to registered critical care nurses working in King Khalid Hospital (KKH), Ha'il, KSA, between July and August 2020. Participant demographics and key variables data related to NPE, job satisfaction and ITL respectively were collected from the participants using existing and validated questionnaires. Descriptive statistics and correlational analysis and multivariable analyses were conducted. Results A response rate of 98% was achieved (152/160) for the study. Findings showed that the NPE was largely favourable (M = 2.89, SD = 0.44); however, nurse participation in hospital affairs (M = 2.83, SD = 0.47) and staffing and resource adequacy (M = 2.88, SD = 0.47) scored lowest. NPE was found to be significantly correlated with job satisfaction (rs = .287, P < .01). A significant negative relationship was found between NPE and ITL (rs = −0.277**, P < .01). However, job satisfaction was associated with ITL (rs = −.007, P = .930). Conclusions Maintaining a healthy work environment and job satisfaction levels in critical care units is key to improving, recruitment and retention of nursing staff. Relevance to clinical practice Critical care and hospital leaders should implement programs that enhance the quality of the practice environment. This will improve nurse participation in unit and hospital affairs, job satisfaction and intention to stay.